IMPLEMENTATION OF USWAH METHOD AT SMPIT AL MUFID BEKASI - ., Sadan; Mujahidin, Endin; Handrianto, Budi (LPPM Univ. Ibn Khaldun Bogor, 2023)
The implementation of the uswah method at SMPIT Al-Mufid is an analysis of teacher activities to improve their role in education at SMPIT Al-Mufid. The analysis used is direct observation and participation. The subjects analyzed were principals, curriculum waka, student waka, teachers, and learners. Data analysis is carried out by selecting the data obtained and then collected for analysis and conclusions are drawn. The results of the implementation of the uswah method at SMPIT Al-Mufid have been going well, the implementation of teacher uswah in learning such as by preceding greetings in every learning session, being on time in every lesson schedule, greeting students, giving rewards and appreciating students with congratulations and other motivational words for outstanding students. The implementation of teacher uswah in discipline as seen in the application of discipline in school, the implementation of teacher uswah in worship such as with the implementation of prayer in congregation and on time, and the implementation of teacher uswah in cleanliness as seen in terms of throwing garbage in its place and picking up existing garbage and throwing it in its place and dressing neatly and cleanly. The implementation of students' attitudes in their daily lives can be seen in that SMPIT Al-Mufid students are very polite and respectful towards their teachers.